TESTING OF MODELS OF BRIDGE DECKS WITH REINFORCED CONCRETE FIXED FORMWORK - Dmytro Kot; Olena Kot (World Science, 2024)
In Ukraine, in the second half of the 20th century, the vast majority of highway bridges span structures were built from precast concrete. This was due to the requirement of construction industrialization in the USSR, which required the maximum use of prefab structures. Therefore, the bridge deck slabs had a significant number of longitudinal joints. The experience of maintenance of bridges prefabricated reinforced concrete span structures has shown that a significant number of defects occur in their slabs due to the presence of joints. Taking into account the above, the current state building regulations of Ukraine for bridge design indicate that in the case of using prefabricated reinforced concrete beams, their surface should be covered with a layer of cast-in-situ reinforced concrete with a thickness of at least 14 cm. Taking these requirements into account, reinforced concrete span structures of highway bridges are arranged mainly precast and cast-in-situ: installing of precast beams, concreting of the cast-in-situ slab above them. This design requires using of formwork for the slab installation. A promising direction in cast-in-situ bridge construction is using of various types of permanent formwork. However, their use has not been studied to date. Having studied the experience of using non-removable formwork, it is proposed to test series of samples to determine the suitability for further operation of one or another option, in addition to studying of the joint operation of non-removable formwork plates as part of the combined cross-section of the deck slab.